Deregulation of education: What does it mean for efficiency and equality? - Raphaela Schlicht-Schmälzle; Janna Teltemann; Michael Windzio (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2011)
This article analyses from a cross-national comparative perspective how deregulation of compulsory education affects two central educational outcomes: efficiency and equality. The conflict between public regulation on the one hand and the market model on the other hand describes one of the most fundamental political struggles. In several fields of societal life, such as compulsory education, the state traditionally holds a strong monopoly in almost all capitalist societies. However, using three waves of PISA school level data we show that the degree of public regulation varies cross-nationally. The central finding of our analyses is that deregulation of education increases educational achievement of individual students across all social classes and thereby fosters the educational efficiency of the national education systems. Nevertheless, it also becomes evident that higher social classes benefit more strongly from deregulation, which increases the degree of educational inequality. These results indeed confirm that deregulation of education provokes an efficiency-versus-equality trade-off in national education systems. – – Der Konflikt zwischen einer staatlichen Regulation schulischer Bildung auf der einen Seite und einem deregulierten Marktmodell auf der anderen Seite stellt eine der fundamentalsten politischen Auseinandersetzungen der letzten Jahrzehnte dar. Traditionellerweise hält der Staat das Monopol der Bildungsorganisation, doch seit einigen Jahren haben verschiedene Länder verstärkt auf eine Privatisierung und Flexibilisierung schulischer Bildung gesetzt. Allerdings variiert der Grad der Standardisierung bzw. Deregulierung über verschiedene nationale Bildungssysteme deutlich. Der Beitrag untersucht mithilfe eines internationalen Vergleichs wie sich eine Deregulierung des schulischen Sektors auf die zentralen bildungspolitischen Outcomes Effizienz (bzw. Leistung) und Chancengleichheit auswirkt. Mit Daten aus drei Wellen der OECD PISA-Studie zeigen wir, dass sich eine Deregulierung des schulischen Sektors positiv auf die Leistungen aller Schüler auswirkt und somit die Effizienz von Bildungssystemen steigert. Allerdings wird auch deutlich, dass höhere soziale Schichten stärker von einer Deregulierung profitieren. Damit bestätigt sich die Annahme, dass die Deregulierung schulischer Bildung zu einem Trade-off zwischen Effizienz und Gleichheit führt.
Keywords: 300